PERAN EKONOMI WANITA DAN KESETARAAN GENDER DALAM BUDAYA KARO - Neila Susanti (Pusat Studi Gender dan Anak, 2020)
The Karo Batak is one of the ethnic Batak groups in North Sumatra. The Karo ethnic group greatly differentiates the position of men and women in their social structure. Differences in treatment of men and women cover various aspects of the life of the Karo ethnic group, namely that only boys can continue their father's clan, only boys become heirs and receive the same share. However, the cultural values in the Karo custom in the field of heritage seem counter-productive to the practices and behavior of the Karo people in the field in several other fields, namely education and economics. From the results of field observations, it can be seen that currently girls from the Karo Batak ethnicity have got the same opportunities as men in terms of higher education. As for the economic sector, Karo women occupy a strategic role in meeting the economic needs of their families. Based on the results of observations and interviews conducted by researchers, a wife does all economic activities with her husband. Starting from hoeing, planting, harvesting, lifting crops, to bringing crops to sell to the market. All these activities are carried out by Karo women as a manifestation of